SAT0251 Predicting and managing primary and secondary non-response to rituximab using b-cell biomarkers in systemic lupus erythematosus. (15th June 2017) - Yusof, MY Md; Shaw, D; El-Sherbiny, YM; Rawstron, AC; Emery, P; Vital, EM
Abstract : Background: Rituximab (RTX) is the most commonly used biologic for the treatment of SLE. However, there is are no clinically applicable predictors of response, which is of particular importance in this heterogeneous disease with other biologics being restricted to certain subgroups. Objectives: To assess factors associated with primary and secondary non-response to RTX in SLE in order to develop more targeted and effective B-cell therapy. Methods: A prospective observational study was conducted in 125 SLE patients treated with RTX in Leeds for over 12 years. A major clinical response was defined as improvement of all active BILAG-2004 domains to grade C/better and no A/B flare. Partial responders were defined by 1 persistent BILAG B. B-cell subsets were measured using highly sensitive flow cytometry. Predictors of response were analysed using logistic regression analysis. Results: 117 patients had evaluable data. In cycle 1 (C1), 96/117 (82%) achieved BILAG response [major=50%, partial=32%]. In MVA, younger age & B-cell depletion at 6 weeks increased the odds of major response (Table 1 ). Complete depletion was predicted by normal complement & lower pre-RTX plasmablasts. 77 (with data on 72) C1 responders were retreated on clinical relapse. Of these, 61/72 (85%) responded in C2. Of 11 C2 non-responders, 9 met secondary non-depletion non response (2NDNR) criteria, as defined by infusion reaction & defective depletion ( incidence=12%) and tested positive for anti-RTX antibodies. Lack of concomitant immunosuppressant & higher pre-RTX plasmablasts predicted 2NDNR. Conclusions: B-cell subsets should be monitored in the routine care of SLE patients receiving RTX and should aim to achieve complete depletion. About 1 in 8 SLE patients lose depletion on repeat cycles and this is associated with anti-RTX antibodies. Clinical trials using more intensive RTX treatment regimens in those predicted not to completely deplete, or alternatively use of humanised anti-CD20mAbs are likely to increase clinical response rates to B-cell depleting agents. Acknowledgements: This research was funded/supported by NIHR (DRF-2014–07–155) and (CS-2013–13–032). The views expressed are those of the author(s) & not necessarily those of the NHS, NIHR or the Dept of Health Disclosure of Interest: None declared